A literature survey on question answering system in natural language processing - Clementeena, A; P. Sripriya, Dr (International Journal of Engineering and Technology, 2018)
In order to respond to usual free form of questions that is contained in a large collection of informative texts or information. For this to hap-pen one must understand what type of questions are being imposed and thus to also know a few knowledge about the process. The con-straints will include the semantic and syntactic knowledge and framing that sort of question with possible correct answers. Thus this paper gives you a clear vision of how its being worked on question answering and thus it presents a machine learning approach. Also ways a important way of giving answers to closed domain in a different data set of know.Â